Impairment in Social Functioning differentiates youth meeting Ultra-High Risk for psychosis criteria from other mental health help-seekers: A validation of the Italian version of the Global Functioning: Social and Global Functioning: Role scales. (July 2017) - Lo Cascio, Nella; Curto, Martina; Pasqualetti, Patrizio; Lindau, Juliana Fortes; Girardi, Nicoletta; Saba, Riccardo; Brandizzi, Martina; Monducci, Elena; Masillo, Alice; Colafrancesco, Giada; Solfanelli, Andrea; De Crescenzo, Franco; et al.
Abstract: Social and occupational impairments are present in the schizophrenia prodrome, and poor social functioning predicts transition to psychosis in Ultra-High Risk (UHR) individuals. We aimed to: 1) validate the Italian version of the Global Functioning: Social (GF: S) and Global Functioning: Role (GF: S) scales; 2) evaluate their association with UHR criteria. Participants were 12–21-years-old (age, mean=15.2, standard deviation=2.1, male/female ratio=117/120) nonpsychotic help-seekers, meeting (N=39) or not (N=198) UHR criteria. Inter-rater reliability was excellent for both scales, which also showed good to excellent concurrent validity, as measured by correlation with Global Assessment of Functioning (GAF) scores. Furthermore, GF:S and GF: R were able to discriminate between UHRs and non-UHRs, with UHRs having lower current scores. After adjusting for current GAF scores, only current GF:S scores independently differentiated UHR from non-UHR (OR=1.33, 95%CI: 1.02–1.75, p=0.033). Finally, UHR participants showed a steeper decrease from highest GF:S and GF: R scores in the past year to their respective current scores, but not from highest past year GAF scores to current scores. GF:S/GS: R scores were not affected by age or sex. GF:S/GF: R are useful functional level and outcome measures, having the advantage over the GAF to not confound functioning with symptom severity. Additionally, the GF:S may be helpful in identifying UHR individuals. Highlights: Reliable measures of functioning are needed in Ultra-High Risk (UHR) research. The Italian version of the Global Functioning: Social scale distinguishes between UHR and non-UHR (OR=1.33, 95%CI: 1.02–1.75, p=0.033). The Global Functioning scales showed excellent reliability and convergent validity. Such measures avoid confounding functioning with symptom severity.